The problem of moral choice personality - I. A. Kadievskaya (Granì, 2014)
Article is dedicated to the comprehension of the problems of the moral selection of personality. It is substantiated, that the moral consciousness is the complex system, because of which in the society are established the specific rules of interrelations between the people.   The concepts are analyzed: morals, relativity, moral absolutism, general human values, globalization, manipulation by consciousness, spiritual moral training. The specific character of the moral relativity, which denies absolute nature, i.e., is established universality and compulsion of morals, emphasizing conditionality and situationality of moral n. Moral absolutism is contradicted to moral relativity. Moral absolutism corresponds to persuasion, that there are absolute standards, which can be used for the permission of questions of morals, and that the specific actions can be correct or incorrect by themselves independent of their context. The twodigit (positive and negative) axiological understanding of the phenomenon of globalization, which dually influences our consciousness, spiritual peace and moral selection, is represented. Under the conditions for largescale information manipulations the translation of moral values as information, modifies their essence. Is shown the role of spiritual moral training in the formation, which must be variative and voluntary, allow for the possibility of ideological selection. The moral freedom of each person is manifested in the transformation of moral requirements into the internal needs of personality, into its own persuasions.